2006
DOI: 10.1073/pnas.0608062103
|View full text |Cite
|
Sign up to set email alerts
|

Self-recognition in an Asian elephant

Abstract: Considered an indicator of self-awareness, mirror self-recognition (MSR) has long seemed limited to humans and apes. In both phylogeny and human ontogeny, MSR is thought to correlate with higher forms of empathy and altruistic behavior. Apart from humans and apes, dolphins and elephants are also known for such capacities. After the recent discovery of MSR in dolphins (Tursiops truncatus), elephants thus were the next logical candidate species. We exposed three Asian elephants (Elephas maximus) to a large mirro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
338
1
11

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 503 publications
(360 citation statements)
references
References 21 publications
(15 reference statements)
10
338
1
11
Order By: Relevance
“…However, the underlying mechanisms involved may be fundamentally Visual self-recognition in gibbons T. Suddendorf & E. Collier-Baker 1675 different. Positive results for one elephant (Plotnik et al 2006), two magpies (Prior et al 2008) and one dolphin (Reiss & Marino 2001) have been reported in the literature. Among primates, only the descendents of a humanoid that probably lived between 13.8 and 18 Myr ago have so far reliably demonstrated that they know who it is that who looks back at them when they look in a mirror.…”
Section: Discussionmentioning
confidence: 92%
“…However, the underlying mechanisms involved may be fundamentally Visual self-recognition in gibbons T. Suddendorf & E. Collier-Baker 1675 different. Positive results for one elephant (Plotnik et al 2006), two magpies (Prior et al 2008) and one dolphin (Reiss & Marino 2001) have been reported in the literature. Among primates, only the descendents of a humanoid that probably lived between 13.8 and 18 Myr ago have so far reliably demonstrated that they know who it is that who looks back at them when they look in a mirror.…”
Section: Discussionmentioning
confidence: 92%
“…If not, it would suggest that the VENs may be related to behavioral specializations common to hominids, whales, and elephants. One such behavioral specialization could be mirror selfrecognition (Reiss and Marino, 2001;Plotnik et al, 2006). However, this awaits confirmation from further studies.…”
Section: Discussionmentioning
confidence: 99%
“…The 4-kg elephant brain is remarkably complex, and in many ways, mirrors our own (14,15). Recent studies put elephant social complexity on a par with that of the great apes, including findings of their capacities for mirror self-recognition, cooperation, empathy, and problem-solving (16)(17)(18)(19)(20). It is then of little surprise that they are learning to adapt to their changing natural environments, but quite disturbing that we are forcing them to do so.…”
Section: Mccomb Etmentioning
confidence: 99%